2021
DOI: 10.1002/ptr.7353
|View full text |Cite
|
Sign up to set email alerts
|

Tectorigenin protects against unilateral ureteral obstruction by inhibiting Smad3‐mediated ferroptosis and fibrosis

Abstract: Renal tubular epithelial cell (TEC) injury and fibrosis are the key factors of the pathogenesis of chronic kidney disease. Here, we reported that tectorigenin is effectively protected against obstructive nephropathy established by unilateral ureteral obstruction (UUO). In vivo, tectorigenin administration significantly alleviated the deteriorations of renal functions including blood urea nitrogen and creatinine. Meanwhile, results from the histology suggested that renal injury characterized by tubular cell dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…Recent studies have demonstrated that liproxstatin-1 attenuates renal fibrosis induced by UUO through inhibiting ferroptosis in renal tubular epithelial cells ( Zhang et al, 2021 ). Ferrostatin-1 is a widely used ferroptosis blocker, which exhibits renoprotective effects in obesity-induced renal fibrosis, inflammatory cell infiltration by inhibiting ferroptosis in high-fat diet mice ( Li et al, 2022 ). It might reverse pathological parameters and improve renal function of folic acid-induced AKI mice, which is a model for studying nephrotoxic tubule damage and gradual progression of renal fibrosis ( Li X. et al, 2020 ).…”
Section: Ferroptosis Regulators and Renal Fibrosismentioning
confidence: 99%
“…Recent studies have demonstrated that liproxstatin-1 attenuates renal fibrosis induced by UUO through inhibiting ferroptosis in renal tubular epithelial cells ( Zhang et al, 2021 ). Ferrostatin-1 is a widely used ferroptosis blocker, which exhibits renoprotective effects in obesity-induced renal fibrosis, inflammatory cell infiltration by inhibiting ferroptosis in high-fat diet mice ( Li et al, 2022 ). It might reverse pathological parameters and improve renal function of folic acid-induced AKI mice, which is a model for studying nephrotoxic tubule damage and gradual progression of renal fibrosis ( Li X. et al, 2020 ).…”
Section: Ferroptosis Regulators and Renal Fibrosismentioning
confidence: 99%
“…In Pdk1 mutant mice, Fer-1 could inhibit ferroptotic cell death, Akt-mediated proliferation, S6, Stat3, and Rb signaling, delaying cyst growth in ADPKD mouse models ( Zhang et al, 2021 ). Treatment of STZ-induced DN animal models with rosiglitazone (an ACSL4 inhibitor), led to a reduction in lipid peroxidation and iron content in the kidneys, improving kidney function ( Bao et al, 2007 ; Wang et al, 2020 ; Li et al, 2022 ). In more recent studies, tectorigenin showed protective effects against kidney injury and fibrosis, two key factors during CKD pathogenesis ( Bebber et al, 2020 ).…”
Section: Targeting Ferroptosis In Chronic Kidney Diseasementioning
confidence: 99%
“…Tectorigenin, a small molecule derived from the medicinal herbal Belamcanda chinensis, has proved to possess protective activities against ferroptosis and fibrosis both in vivo and in vitro, which is mediated by Smad3-induced expression of NADPH oxidase 4 (NOX4). 84 Nobiletin, a flavonoid in the peel of citrus fruits, ameliorates ferroptosis-associated injury and renal fibrosis in the kidney of UUO mice, suggesting that Nob treatment has anti-ferroptosis and antifibrotic effects. 85 Pretreatment of FG-4592, an inhibitor of prolyl hydroxylase of HIF, plays a protective role in the early stage of folic acid-induced kidney injury and retards the progression of renal fibrosis, mainly by alleviating ferroptosis via stabilizing HIF-1α and Akt/GSK-3βmediated Nrf2 activation.…”
Section: Ferroptosis and Renal Fibrosismentioning
confidence: 99%